China’s strategic goals and positions in international organizations: China’s strategic goals and positions in international organizations - Aldabek, N.A.; Iskakova, Z. (Journal of Oriental Studies, 2022)
The article analyzes China’s strategic goals and positions in relation to international organizations, examines the features and advanced political principles in conducting foreign policy. According to China, its main mission in the international arena is to maintain peace on earth and support common development. He has always been a supporter of peaceful coexistence with neighbors, and this is the main principle of the Celestial Empire in building international relations. In the conditions of modern globalization, the role of international organizations in the international arena and their influence on world political processes is increasing. For China, which is looking for its place in the post-bipolar world, first of all, international organizations that are able to conduct an equal dialogue with partners from China and effectively defend their national interests are of great interest. But many states that have been observing China’s bilateral policy are making contact with China step by step and suspiciously. Every State that adheres to the principle that we support peace and mutual development is really working in its own interests. That is, the attitude “there is no friendship between states, there is a common interest” is the main position of China’s policy towards international organizations. Key words: People’s Republic of China, international organizations, political principles, strategy, hegemonism